The Effectiveness of Thunkable-Based Mobile Learning on Arabic Vocabulary Mastery - Nanang Kosim; Eva Latifah Fauzia; Dini Nur Annisa; Jimmy Surya Nugraha; Ahmad Aljanadbah (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2025)
The integration of mobile technology in elementary Arabic language learning has increased; however, empirical studies examining the effectiveness of customizable app-development platforms for vocabulary instruction remain limited and underexplored. This study aims to examine the effectiveness of a Thunkable-based mobile learning application in improving Arabic vocabulary mastery among fifth-grade students at Madrasah Ibtidaiyyah Matlaul Athfal Cilengkrang, Bandung. Addressing the limited empirical studies on the use of app-development platforms for elementary-level Arabic instruction, this research employed a quantitative quasi-experimental design with a non-equivalent control group. A total of 41 students participated, comprising an experimental group (n = 20) and a control group (n = 21). Data were collected through pre- and post-tests and analyzed using descriptive statistics, paired-sample and independent-sample t-tests, as well as N-Gain analysis. The results showed a statistically significant improvement in the experimental group’s vocabulary mastery compared to the control group (p < 0.05). The experimental group achieved a moderate N-Gain score (55.75%), while the control group demonstrated a lower level of improvement (34.43%). These findings indicate that Thunkable-based mobile learning is an effective and interactive medium for enhancing Arabic vocabulary acquisition at the elementary level. The study contributes to research on mobile-assisted language learning by demonstrating the pedagogical potential of customizable mobile applications in Arabic language education. It offers practical implications for teachers integrating digital learning tools.